QoS-Aware Congestion Adaptive Routing for streaming multimedia in Mobile Ad hoc Networks. (26th January 2010) - Ramesh, B.; Manjula, D.
Present routing protocols are finding feasible route without considering current traffic and QoS requirements of application. Due to mobility and congestion, more packet loss, longer delay for streaming multimedia. Multimedia applications require QoS support to avoid congestion. QoS Aware Congestion Adaptive Routing (QACAR) can achieve such properties by selecting route that can satisfy the requirements of applications. We incorporate admission control mechanisms to check the status of network traffic and adapt to congestion. The simulations show that the proposed method can increase throughput and reduce both packet loss and delay. Hence, QACAR is an effective routing to provide QoS guarantee and adapt to network congestion.